Desafios da real política industrial brasileira do século XXI - Mansueto Almeida (Instituto de Pesquisa Econômica Aplicada (IPEA), 2009)
– This paper debates some dilemmas involved in today`s Brazilian industrial policy. First, I will explain the current industrial policy debate in Brazil, stressing the dilemmas involved in supporting the development of technology-intensive sectors in a highly diversified economy led by low and medium-low technology intensive sectors. Second, despite the current discourse to foster innovation across the sectors, Brazilian government continues to promote specific sectors and firms as it did back in the import substitution period. In spite of that, seldom does the government recognize this real industrial policy, in which the official discourse pro innovation goes hand in hand with traditional industrial policies of picking up the winners. Third, I show that the real industrial policy in Brazil, when necessary, tends to discriminate against foreign-owned firms in some sectors to build national large firms. And last, I argue that today`s industrial policy in Brazil still occurs in an environment in which capitalists prefer to invest in their private access to state actors instead of investing in collective action through business associations.
Keywords: O14; O16; O25; 330; Industriepolitik; Brasilien